Penyelenggaran Tajen: Judi Versus Sarana Pemasukan Bagi Desa Adat dan Masyarakat - Kairavani, K. Vimala (JURNAL ILMIAH SOSIOLOGI (SOROT), 2014)
ABSTRACT Tajen is a way of balinese tradition who came from tabuh rah ritual. The change of tabuh rah into tajen caused by gambling folks manners. Tajen as a cultural practices is forbidden by canon law and government policy, but Balinese peoples have disobey the orders. Even tajen is a part of gambling, many peoples depends on it.